2021
DOI: 10.3390/polym13060966
|View full text |Cite
|
Sign up to set email alerts
|

Steady and Oscillatory Shear Flow Behavior of Different Polysaccharides with Laponite®

Abstract: The rheological behavior, in terms of steady and oscillatory shear flow, of Laponite® with different polysaccharides (alginate, chitosan, xanthan gum and levan) in salt-free solutions was studied. Results showed that a higher polymer concentration increased the zero-rate viscosity and decreased the critical strain rate (Cross model fit) as well as increasing the elastic and viscous moduli. Those properties (zero-rate viscosity and critical strain rate) can be a suitable indicator of the effect of the Laponite®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In contrast, the other formulation was characterized by a bigger size and a Z potential closer to zero, which probably meant that some particles agglomerated, creating a resistance to flow and therefore obtaining higher values of viscosity. Figure 3 b displays the small-amplitude oscillatory flow results [ 38 ], evaluating the elastic and viscous modulus (G′ and G″, respectively) vs. frequency-flow (ω). Both optimal fluids demonstrated the same viscoelastic behavior; however, the elastic modulus predominated at all evaluated frequencies (G′ > G″) mainly due to the entanglement between biopolymers and clay in the dispersions [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the other formulation was characterized by a bigger size and a Z potential closer to zero, which probably meant that some particles agglomerated, creating a resistance to flow and therefore obtaining higher values of viscosity. Figure 3 b displays the small-amplitude oscillatory flow results [ 38 ], evaluating the elastic and viscous modulus (G′ and G″, respectively) vs. frequency-flow (ω). Both optimal fluids demonstrated the same viscoelastic behavior; however, the elastic modulus predominated at all evaluated frequencies (G′ > G″) mainly due to the entanglement between biopolymers and clay in the dispersions [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results demonstrated that all investigated hydrogels and cryogels exhibited shear-thinning behavior, which is characterized by a reduction in the viscosity with an increase in the shear stress gradient and indicates their non-Newtonian nature. This phenomenon is typical to polymer solutions and expresses the character of a pseudo-plastic fluid where the viscosity is decreased under the influence of shear [ 28 ]. The shear-thinning phenomenon is an important parameter for topical application—it enables the thin gel layer formation on the skin during application [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of clay (Figure 4b), the PVA-PVA interactions are slowly pertur The rheological behavior of entangled polymer solutions is not significantly affected by the presence of Laponite ® RD, because the chain entanglements hinder the formation of the platelet structure [40]. However, the addition of clay to polysaccharide-based systems determines qualitative changes in the flow behavior and mechanical spectra [41,42].…”
Section: Viscoelastic Behavior Of Hydrogelsmentioning
confidence: 99%
“…The manifestation of attractive and repulsive interactions between particles can lead to arrested states (either attractive gel or repulsive glass), generating a variety of rheological behaviors, from quasi-Newtonian to viscoelastic and shear thinning fluids [43]. The rheological behavior of entangled polymer solutions is not signifi by the presence of Laponite ® RD, because the chain entanglements hinder of the platelet structure [40]. However, the addition of clay to polysacchar tems determines qualitative changes in the flow behavior and mechanical s It was also shown that the structural state of Laponite ® RD dispersions de concentration and ionic strength [38,43].…”
Section: Viscoelastic Behavior Of Hydrogelsmentioning
confidence: 99%